Comparison of two different microbiological test kits for detection of periodontal pathogens - Cosgarea, Raluca; Bäumer, Amelie; Pretzl, Bernadette; Zehaczek, Sven; Kim, Ti-Sun (Acta odontologica Scandinavica, 2010)
OBJECTIVE: The aim of this study was to compare the outcome of two different microbiological tests for detection of Aggregatibacter actinomycetemcomitans (A.a.), Porphyromonas gingivalis (P.g.), Tannerella forsythia (T.f.) and Treponema denticola (T.d.). - MATERIAL AND METHODS: A total of 69 adult patients with severe chronic (sCP) or aggressive periodontitis (AgP) participated in the study. Microbiological samples were examined for A.a., P.g., T.f. and T.d. using an RNA probe test (PADO) and a real-time polymerase chain reaction test (MERI). - RESULTS: For all periodontal pathogens under investigation, the median bacterial counts detected with PADO were smaller compared to those detected with MERI. P.g., T.f. and T.d. could be found in the majority of all patients with both tests. With MERI, A.a. was detected more often (24.6%) than with PADO (18.8%). Only 10.1% of the patients tested positive for A.a. with both tests. - CONCLUSION: Both tests showed a high percentage of agreement for P.g., T.f. and T.d., but exhibited marked differences in the detection of A.a.
Gesehen am 22.06.2023